Thomas' Calculus 13th Edition

Published by Pearson
ISBN 10: 0-32187-896-5
ISBN 13: 978-0-32187-896-0

Chapter 3: Derivatives - Section 3.2 - The Derivative as a Function - Exercises 3.2 - Page 115: 2



Work Step by Step

Consider $F(x)=(x-1)^2+1=x^2-2x+2$ and $F'(x)=2x-2$ Now, $F'(-1)=2\times(-1)-2=-4 ; \\F'(0)=2\times(0)-2=-2 ; \\F'(2)=2\times(2)-2=2$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.